Genetic services for Hereditary Cancer: a systematic review of Patient Reported Outcomes studies. (13th November 2019) - Pitini, E; D'Andrea, E; Rosso, A; Massimi, A; Unim, B; De Vito, C; Marzuillo, C; Villari, P
Abstract: Background: Genetic services for Hereditary Breast and Ovarian Cancer (HBOC) have become part of clinical and public health practice. Nevertheless, the evaluation of such services, including genetic testing and counseling, is challenging as they rarely affect health status measures (e.g. mortality and morbidity). A possible way is using Patient Reported Outcomes (PROs) i.e. subjective reports coming from patients, directly attributable to genetic services. We performed a systematic review to explore the use of PROs in HBOC genetic services. Methods: We searched Pubmed, Scopus, and ISI Web of Knowledge for observational studies using PROs to assess standard genetic counseling (i.e. in person and individual) for HBOC. Results: We identified ten surveys from various countries (USA n = 5; Europa n = 6), published between 2000 and 2018 and mainly conducted in Teaching hospitals and Cancer Research and Treatment Institutes (n = 9). The majority assessed pre-test counseling (n = 6) with diagnostic or predictive purpose. The most frequently measured outcomes were patient satisfaction (n = 9), adherence to recommended interventions (n = 3), information sharing with relatives (n = 3); disease risk perception (n = 2), and psychosocial distress (n = 2). Six studies adopted standardized PROs collection tools: the most common were the Genetic Counseling Satisfaction Scale and the Hospital Anxiety and Depression Scale. Questionnaires were mainly administered by post, soon after genetic counseling or up to seven years later. Overall, patients seem satisfied with genetic counseling. Nevertheless, more attention to the psycho-social aspects of genetic testing is needed. Conclusions: PROs are very promising for the assessment of HBOC genetic services. Their routine use could provide important elements to improve the quality and the patient-centeredness of genetic services. Emerging information and communication technologies will help this process by making it easier collecting patient data. Key messages: Precision medicine, where medical decisions are tailored to an individual's characteristics, including the patient's genetic profile, is becoming a paradigm for chronic diseases, particularly cancer. PROs are expected to be increasingly used as a measure of performance in order to drive the changes in how clinical genetic services, and healthcare in general, are organized, delivered and founded.